Awareness and acceptance of human papillomavirus (HPV) vaccination among males attending a major sexual health clinic in Wuxi, China: A cross-sectional study. Issue 6 (2nd June 2016) - Zou, Huachun; Meng, Xiaojun; Jia, Tianjian; Zhu, Chen; Chen, Xin; Li, Xiaolin; Xu, Junjie; Ma, Wei; Zhang, Xuan
ABSTRACT: Objective: To study the awareness and acceptance of human papillomavirus (HPV) vaccination among sexually active men having sex with men (MSM) and men not having sex with men (MNSM) attending the largest sexual health clinic in Wuxi, China. Methods: A questionnaire about participants' socio-demographic characteristics and view on HPV vaccination was collected. Results: A total of 186 MSM and 182 MNSM were recruited. Among MSM, 12.4% were under 20 years old, 64.5% never married and 56.5% from Jiangsu Province (where Wuxi City is located); 64.0% had resided in Wuxi for over 2 years, 64.5% had high school education or more, and 83.9% had an income of 5000 RMB or less per month compared to figures of 5.5%, 50.6%, 73.6%, 54.9%, 86.8% and 64.8% among MNSM, respectively (All P values < 0.05). Among these 2 groups of men, 18.4% and 23.1% had heard of HPV; 10.2% and 15.4% had heard of HPV vaccine; and 26.2% and 20.2% would take HPV vaccine before sexual debut, respectively. MNSM were significantly more willing to take HPV vaccine than MSM (70.9 vs 34.9%, p < 0.001). Factors associated with HPV vaccine acceptance among MSM included engaging mostly in receptive anal sex (Odds ratio (OR)=3.9, 95% Confidence interval (CI): 1.8–13.5), never using a condom in anal sex in the past 6 months (3.5, 1.5–20.2), ever diagnosed with a sexually transmitted infection (STI) (3.4, 1.3–8.4) and ever receiving HIV related services (1.6, 1.1–4.4). Among MNSM these Factors included commercial sex with women (1.7, 1.2–8.6), never using a condom in commercial sex (1.6, 1.4–7.6) and STI diagnosis (2.0, 1.6–7.3). Conclusions: Sexually active MSM and MNSM in Wuxi lacked knowledge of HPV and HPV vaccination. The majority of these at-risk men would not benefit from HPV vaccination as their age at first sex proceeded perceived age of vaccine uptake. Aggressive education aimed at increasing knowledge of HPV and HPV vaccination among these men is warranted.